2020
DOI: 10.3390/ani10122219
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Variance Components and Genomic Prediction for Individual Birth Weight Using Three Different Genome-Wide SNP Platforms in Yorkshire Pigs

Abstract: This study estimates the individual birth weight (IBW) trait heritability and investigates the genomic prediction efficiency using three types of high-density single nucleotide polymorphism (SNP) genotyping panels in Korean Yorkshire pigs. We use 38,864 IBW phenotypic records to identify a suitable model for statistical genetics, where 698 genotypes match our phenotypic records. During our genomic analysis, the deregressed estimated breeding values (DEBVs) and their reliabilities are used as derived response v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Uemoto et al identified six significant quantitative trait loci for immune-related traits in pigs affected by mycoplasma pneumonia of swine using GWAS, revealing novel insights into the genomic elements influencing pig production, respiratory illness, and immunerelated traits (98). Another GWAS-based study identified candidate genes for milk production traits in Korean Holstein cattle and individual birth weight traits in Korean Yorkshire pigs (99,100). Therefore, GWAS-based approaches have potential to decode important and complex traits linked with livestock productivity.…”
Section: Genome Wide Association Study For Identification Of Importan...mentioning
confidence: 99%
“…Uemoto et al identified six significant quantitative trait loci for immune-related traits in pigs affected by mycoplasma pneumonia of swine using GWAS, revealing novel insights into the genomic elements influencing pig production, respiratory illness, and immunerelated traits (98). Another GWAS-based study identified candidate genes for milk production traits in Korean Holstein cattle and individual birth weight traits in Korean Yorkshire pigs (99,100). Therefore, GWAS-based approaches have potential to decode important and complex traits linked with livestock productivity.…”
Section: Genome Wide Association Study For Identification Of Importan...mentioning
confidence: 99%
“…Live weight is an important indicator of livestock productivity and serves as an informative feature for the health, feeding, breeding [1], and selection of livestock [2]. The prediction of live animal weight based on different body characteristics observed during different growth periods for sheep [3], goats [4], chickens [5], ducks [6], rams [7], and cattle [8] has been extensively studied in the literature.…”
Section: Introductionmentioning
confidence: 99%